Os documentários do IPES e a campanha ideológica: as práticas audiovisuais e a preparação do golpe de 1964 - Gaspar, Danielle Morais (2012)
Among 1962 and 1964, the IPES (Instituto de Pesquisa e Estudos Sociais) used the media to promote an ideological campaign materialized in a fighting speech against the labor policy represented by Joao Goulart. The proposal of this research is to study the documentaries mediation process made by IPES, sponsor by the Brazilian industrial elite, in order to alert‟ and mobilize the audience about the communist tendencies that linked to the government. Focusing on the newsreel experience, we seek from the hypothesis that the audiovisual practices were decisive to strengthening a conservative signs system in this society, for the purpose of make it hegemonic and enable the military blow in 1964. It is for this reason that the study of IPES documentaries requires inquire the space production as well as the time and consumption production, both articulated in the everydayness (customs and practices), and the specific technological device in question. Our research strategy avoids analyzes solely focused on the aspects of emission/reception by considering them unsuitable due to its binary simplification in a scenario of multiple overlaps. Therefore, the methodology was built considering that the IPES documentaries used audiovisual practices to strengthen certain themes and values operating in society at the time. This dynamic reduced the culture to an imprinting (Morin), in this case, institutional and ideological. In this sense, concepts such as semiosphere (Lotman), mediation (Martín-Barbero) and semiopragmatic (Odin) are also in this study. Altogether the IPES produced 20 documentaries of which 14 are restored and available at Arquivo Nacional, as well as official documents. Taking advantage of a legal decree nº 21.240, 1932, which required cinemas to stream national productions before the main attractions, in this case, foreign production films and the Jean Manzon network distribution the documentaries had been exhibited all around the country. The research reveals that the convergence of a diachronic axis, located at the practice of newsreel and the political and cultural context, with a synchronic axis that relates the documentary specificities in a certain use was decisive to enhance a speech focus on Nation defense. By strengthening a conservative signs system in this society, the IPES documentaries helped to institutionalize a frightening backdrop against the red menace that triggered on years of military dictatorship in Brazil